Prognosis and Disease Activity - (:unkn) unknown (Springer Nature, 2021)
Correct assessment of the extent of arterial involvement, clinical activity and damage in Takayasu’s Arteritis (TAK) is essential for treatment or surgical intervention decisions during the disease course [1]. However, there are no widely accepted and validated definitions of “disease activity” or “response to treatment”. One of the major difficulties is the differentiation between ongoing activity and vascular damage in TAK. Vascular stenosis may occur as a result of active inflammation or be a sign of disease-related damage due to scarring in the vessel wall [2]. Atherosclerosis is another important clinical problem in the assessment of TAK, especially in patients having long-standing disease or normal acute-phase response. There is a clear need and ongoing efforts to develop a validated set of outcome measures for use in clinical trials of TAK. © 2021, Springer Nature Switzerland AG.
Keywords: Damage; Disease assessment; Prognosis